Comparison of ultrasound features and lesion sites in dysfunctional arteriovenous fistula - Yin Wang; Xiao-mei Huang; Yi Zhang; Jingjing Li; Jun Li; Zheng Ye; Yu Peng; Xian-jin Zhang; Na Tang; Wen-wen Qiu; Li Xu (Renal Failure)
This study aimed to investigate ultrasound features of arteriovenous fistula stenosis and their relationship with primary patency after percutaneous transluminal angioplasty (post-intervention primary patency) and compare this classification with that using lesion location. Hemodialysis patients who underwent ultrasound-guided percutaneous transluminal angioplasty for arteriovenous fistula stenosis from July 2020 to December 2021 were retrospectively evaluated. Lesions (excluding inflow arteries) were categorized into five groups based on ultrasound features, and the clinical characteristics and risk factors affecting the post-intervention primary patency of the arteriovenous fistula were analyzed. Among 185 patients, 100 (54.05%), 36 (19.46%), 22 (11.89%), 11 (5.95%), and 16 (8.65%) were classified into the intima-dominant, non-intima-dominant, valve obstruction, vascular calcification, and mixed groups, respectively. The dialysis duration and arteriovenous fistula use time were the highest in the vascular calcification group at 86 (interquartile range: 49–140) and 77 (interquartile range: 49–110) months, respectively. Diabetes mellitus was most common in the intima-dominant group (42.0%). In Kaplan–Meier and univariate Cox analysis, type III lesion location (stenosis in the venous confluence site) was associated with the lower post-intervention primary patency. In the multivariate Cox analysis, percutaneous transluminal angioplasty times (the number of times patients were treated with percutaneous transluminal angioplasty for arteriovenous fistula stenosis dysfunction), vascular calcification, calcification at the lesion site requiring percutaneous transluminal angioplasty, and serum parathyroid hormone levels were independent risk factors for post-intervention primary patency. Ultrasound features showed that calcification of the arteriovenous fistula was detrimental to the post-intervention primary patency of arteriovenous fistula.